A checklist of the genus Cyanus (Asteraceae, Cardueae) in Turkey, with notes on taxonomy and distribution - Negaresh, Kazem (Phytotaxa, 2022)
A taxonomic synopsis of the genus Cyanus in Turkey is presented. Cyanus hekimhanensis, C. cheiranthifolius var. purpurascens and C. reuterianus var. phrygius are proposed as new combinations. Some new synonymizations are proposed: Centaurea cana var. sultanensis with C. matthiolifolius, Centaurea pichleri var. ancyrensis with C. pichleri, Centaurea cana f. fulgens with C. triumfettii. Cyanus akcadaghensis is a synonym of C. matthiolifolius, Cyanus ermenekensis is a synonym of C. reuterianus, Cyanus banchevae is a synonym of C. thirkei. Lectotypes are designated here for ten accepted or synonymed names. The recognized taxa, the relevant synonyms, type details, lists of specimens examined, and a taxonomic key are provided for this genus in Turkey. In addition, the geographic distribution of all the taxa recognized in Turkey is presented and mapped.